1985
DOI: 10.1017/s0022215100097231
|View full text |Cite
|
Sign up to set email alerts
|

Extracochlear eight-channel electrode system

Abstract: SummaryThe Cologne-Diiren research group has developed a new extracochlear eight-channel electrode system. The first observations on six cases have shown encouraging psychoacoustic results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2000
2000
2003
2003

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…Each electrode carried speech information from third-octave band-pass filters. In 1984, 46 patients had the operation (Banfai et al 1986;Banfai 1987). Although studies showed that pitch discrimination could be obtained by extracochlear stimulation at different sites over the cochlea (Banfai et al 1986), this was not conclusive.…”
Section: Cologne-dürenmentioning
confidence: 99%
See 4 more Smart Citations
“…Each electrode carried speech information from third-octave band-pass filters. In 1984, 46 patients had the operation (Banfai et al 1986;Banfai 1987). Although studies showed that pitch discrimination could be obtained by extracochlear stimulation at different sites over the cochlea (Banfai et al 1986), this was not conclusive.…”
Section: Cologne-dürenmentioning
confidence: 99%
“…In 1984, 46 patients had the operation (Banfai et al 1986;Banfai 1987). Although studies showed that pitch discrimination could be obtained by extracochlear stimulation at different sites over the cochlea (Banfai et al 1986), this was not conclusive. In a larger group of patients the author reported that "11% of the first 129 implantees showed some signs of developing open-speech perception" (Banfai 1987).…”
Section: Cologne-dürenmentioning
confidence: 99%
See 3 more Smart Citations